The Critique of Digital Capitalism: An Analysis of the Political Economy of Digital Culture and Technology - Betancourt, Michael (punctum books, 2016)
Anything that can be automated, will be. The "magic" that digital technology has brought us - self-driving cars, Bitcoin, high frequency trading, internet of things, social networking, mass surveillance, the 2009 housing bubble - has not been considered ideologically. The Critique of Digital Capitalism identifies how digital technology has captured contemporary society in a reification of capitalist priorities. The theory proposed in this book is the description of how digital capitalism as an ideologically "invisible" framework is realized in technology. Written as a series of articles between 2003 and 2015, it provides a broad critical scope for understanding the inherent demands of capitalist protocols for expansion without constraint (regardless of social, legal or ethical limits) that are increasingly being realized as autonomous systems no longer dependent on human labor or oversight and implemented without social discussion of their impacts. The digital illusion of infinite resources, infinite production, and no costs appears as an "end to scarcity," whereby digital production supposedly eliminates costs and makes everything equally available to everyone. This fantasy of production without consumption hides the physical costs and real-world impacts of these technologies.